Epidemiology of endemic systemic fungal infections in Latin America - Colombo, Arnaldo Lopes [UNIFESP] (2011)
Although endemic mycoses are a frequent health problem in Latin American countries, clinical and epidemiological data remain scarce and fragmentary. These mycoses have a significant impact on public health, and early diagnosis and appropriate treatment remain important. the target population for endemic disease in Latin America is mostly represented by low-income rural workers with limited access to a public or private health system. Unfortunately, diagnostic tools are not widely available in medical centers in Latin America; consequently, by the time patients are diagnosed with fungal infection, many are already severely ill. Among immunocompromised patients, endemic mycoses usually behave as opportunistic infections causing disseminated rather than localized disease. This paper reviews the epidemiology of the most clinically significant endemic mycoses in Latin America: paracoccidioidomycosis, histoplasmosis, and coccidioidomycosis. the burdens of disease, typically affected populations, and clinical outcomes also are discussed.